2015
DOI: 10.1186/s40880-015-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

SHMT1 C1420T polymorphism contributes to the risk of non-Hodgkin lymphoma: evidence from 7309 patients

Abstract: BackgroundSerine hydroxymethyltransferase 1 (SHMT1) is a key enzyme in the folate metabolic pathway that plays an important role in biosynthesis by providing one carbon unit. SHMT1 C1420T may lead to the abnormal biosynthesis involved in DNA synthesis and methylation, and it may eventually increase cancer susceptibility. Many epidemiologic studies have explored the association between C1420T polymorphism and the risk of non-Hodgkin lymphoma (NHL), but the results have been contradictory. Therefore, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 27 , 28 Additionally, polymorphisms in the SHMT1 gene have been shown to be associated with a wide variety of cancers, including childhood acute lymphoblastic leukemia, non-Hodgkins lymphoma, head and neck cancers, and colon cancer. 29 , 30 , 31 , 32 In this study, we identified SHMT1 as a new regulator of ovarian cancer tumor growth and progression.…”
Section: Discussionmentioning
confidence: 92%
“… 27 , 28 Additionally, polymorphisms in the SHMT1 gene have been shown to be associated with a wide variety of cancers, including childhood acute lymphoblastic leukemia, non-Hodgkins lymphoma, head and neck cancers, and colon cancer. 29 , 30 , 31 , 32 In this study, we identified SHMT1 as a new regulator of ovarian cancer tumor growth and progression.…”
Section: Discussionmentioning
confidence: 92%
“…Genetic variation plays an important role in HCC susceptibility and disease development (25). As the key enzymes in one-carbon metabolism, SHMT1/2 are essential for dNTP synthesis (26,27). Previous studies have shown that the expression level and activity of SHMT1/2 are closely associated with the occurrence and development of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis was performed by cancer type (if one cancer type contained only one study, it would be merged into the “other” group), ethnicity, and sample size (<500 and ≥500). Sensitivity analysis was used to evaluate the effect of individual investigations on the overall cancer risk by excluding each investigation individually and recalculating the ORs and the 95% CIs [27]. All the statistical tests were performed with Stata (version 12.0; Stata Corporation, College Station, TX).…”
Section: Methodsmentioning
confidence: 99%